Gold-stamped anti-oxidation alumite film and gold-stamped printed matter

By introducing anti-oxidation graphene film layer and protective layer into the hot stamping electrolytic aluminum film, the oxidation corrosion and paste problems caused by hot stamping temperature are solved, the hot stamping quality and pattern clarity are improved, and efficient physical isolation is achieved and antioxidant effects.

CN119116580APending Publication Date: 2024-12-13SUZHOU MYS ENVIRONMENTAL PROTECTION & TECH CO LTD

Patent Information

Application Number
CN202411398622.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

After the conventional electrochemical aluminum hot stamping is on the surface of paper substrate, the silicone resin shedding layer and adhesive are over-melted due to the high temperature, causing the electrochemical aluminum to fall off around the mark, and the aluminum layer to oxidize and corrode, affecting the quality and brightness of the hot stamping.

Method used

Design a gold-stitched anti-oxidation electrochemical aluminum film. Graphene has chemical inertness and high thermal conductivity by setting an anti-oxidation graphene film layer between the aluminum plating layer and the glue layer, and adding a protective layer between the release layer and the color layer. Avoid oxidation corrosion and paste.

Benefits of technology

Effectively prevent oxidative corrosion of the aluminum layer, improve the quality of hot stamping, avoid blisters or mist patterns, enhance pattern clarity and wear resistance, reduce production costs, and maintain environmentally friendly film preparation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119116580A_ABST
    Figure CN119116580A_ABST
Patent Text Reader

Abstract

The invention relates to a gold-stamped anti-oxidation alumite film and a gold-stamped printed matter, the gold-stamped anti-oxidation alumite film comprises a base material film layer, a release layer, a color layer, an aluminum-plated layer and a glue layer which are connected in sequence, and an anti-oxidation graphene film layer is arranged between the aluminum-plated layer and the glue layer. Thus, the anti-oxidation graphene film layer is arranged between the aluminum-plated layer and the adhesive layer, the main component of the anti-oxidation graphene film layer is graphene, graphene does not react with acid and alkali, and excellent chemical inertness and chemical stability are achieved; meanwhile, the graphene also has in-plane impermeability, so that substances in the solution cannot permeate, and excellent physical isolation and anti-oxidation effects can be achieved. The high thermal conductivity of the graphene can also avoid the problem of poor heat dissipation of the substrate caused by the addition of the coating. Through the arrangement of the anti-oxidation graphene film layer, the technical problem that oxidation occurs after conventional alumite gold stamping is well solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of hot stamping technology, and in particular to a hot stamping anti-oxidation electrochemical aluminum film and hot stamping printed products. Background Art

[0002] Hot stamping is also called hot stamping of anodized aluminum, and the hot stamping material used is anodized aluminum. Hot stamping uses the principle of heat transfer to transfer anodized aluminum to the surface of the substrate. The basic process is: the anodized aluminum material is heated to melt its hot-melt silicone resin layer and adhesive when it is pressed by the hot stamping plate and the substrate. At this time, the viscosity of the melted silicone resin decreases, while the viscosity of the special heat-sensitive adhesive increases after being melted by heat, so that the aluminum layer is peeled off from the anodized aluminum base film and transferred to the substrate at the same time. As the pressure is removed, the adhesive quickly cools and solidifies, and the aluminum layer is firmly attached to the substrate, completing the hot stamping process.

[0003] However, due to the limitations of production processes and technologies, after conventional electroplated aluminum hot stamping foil is hot stamped on the surface of some paper substrates, the printed images and texts are affected by the environment and the high hot stamping temperature during the hot stamping production, which causes the silicone resin to fall off the layer and the adhesive to melt excessively, causing the electroplated aluminum attached to the imprint to melt and fall off, resulting in a paste plate. At the same time, high temperature will also cause the synthetic resin and dye in the color layer to oxidize and polymerize, the imprint will bubble or appear foggy, and the aluminum layer will experience varying degrees of oxidation corrosion, which will reduce the brightness of the hot stamped products or lose their metallic luster, causing economic losses to the company.

[0004] Patent document CN106113961A discloses an electrochemical aluminum foil film for hot stamping, which is composed of a base PE film, a separation coating, a color coating, a metal aluminum coating and a glue coating, which are compounded and bonded with polypropylene liquid spraying between each two layers. The present invention uses a multi-layer composite of an electrochemical aluminum foil film, and uses polypropylene to compound between each two composite layers. The connection is stable when drying, and it is easy to separate after heating. The glue coating is made by mixing a variety of materials, so that the metal aluminum layer is firmly bonded to the surface of the hot stamping object after hot stamping, and graphene is added to the metal aluminum layer to ensure that the pattern is clear after hot stamping. However, although a small amount of graphene powder is added to the metal aluminum coating to improve the pattern effect in the above-mentioned document, when the hot stamping temperature is too high, it is still easy to have a silicone resin shedding layer and excessive melting of the adhesive, so that the electrochemical aluminum attached to the imprint around is also melted and falls off to produce a paste version, and the aluminum layer is still prone to oxidation corrosion, thereby affecting the hot stamping quality. Summary of the invention

[0005] Based on this, it is necessary to provide a hot stamping anti-oxidation electrochemical aluminum film and hot stamping printed products that can solve the problem of plate sticking, the problem of bubbling or fogging of prints, the problem of oxidation corrosion of the aluminum layer, and can improve the quality of hot stamping.

[0006] In a first aspect, the present application provides a hot stamping anti-oxidation electrochemical aluminum film, comprising a substrate film layer, a release layer, a color layer, an aluminum coating layer and an adhesive layer connected in sequence, characterized in that an anti-oxidation graphene film layer is provided between the aluminum coating layer and the adhesive layer. The present application solves the technical problem of oxidation after conventional electrochemical aluminum hot stamping by providing an anti-oxidation graphene film layer.

[0007] In one embodiment, a protective layer is provided between the release layer and the color layer. The present application provides a protective layer to better solve the problem of plate sticking and the problem of bubbling or fogging of prints.

[0008] In one embodiment, the thickness of the anti-oxidation graphene film layer is 5-15 microns, and preferably, the thickness of the anti-oxidation graphene film layer is 12 microns.

[0009] In one embodiment, the method for preparing the graphene oxide film layer is as follows:

[0010] The graphene oxide solid is dispersed in ultrapure water, and then drop-coated on a PTFE film, dried at high temperature, and separated from the PTFE film to obtain the graphene oxide film layer.

[0011] In one embodiment, the mass volume ratio of the graphene oxide solid to the ultrapure water is: 0.1-0.2 g: 100 ml;

[0012] Preferably, the mass volume ratio of the graphene oxide solid to the ultrapure water is: 0.15g:100ml.

[0013] In one embodiment, the preparation method of the graphene oxide solid is as follows:

[0014] NaNO3, graphite and H2SO4 are mixed, KMnO4 is added, ultrapure water is added dropwise after the reaction, and the mixture is heated for reaction. After cooling to room temperature, H2O2 is added; after standing, the mixture is centrifuged to remove the liquid to obtain a precipitate, hydrochloric acid is added to the precipitate, the mixture is mixed and centrifuged again, the precipitate is diluted to a neutral pH, and then freeze-dried to prepare the graphene oxide solid.

[0015] In one embodiment, the preparation method of the graphene oxide solid is as follows: NaNO3, graphite, and H2SO4 are mixed in an ice bath, KMnO4 is added and reacted in an ice bath for 5-6 hours, the temperature is raised to 35±3°C and the reaction is carried out for 45 minutes, ultrapure water is added dropwise after the reaction, and the mixture is heated to 100°C and reacted for 30 minutes, ultrapure water is added dropwise to the reaction solution, and H2O2 is added slowly and uniformly after cooling to room temperature; after standing, the mixed solution is centrifuged to remove the liquid to obtain a precipitate, 4 vol% hydrochloric acid is added to the precipitate, the mixture is mixed and centrifuged again, the precipitate is aqueous to a neutral pH, and then freeze-dried to obtain the graphene oxide solid.

[0016] In one embodiment, in the method for preparing graphene oxide solid, the mass volume ratio of NaNO3, graphite, H2SO4, KMnO4: H2O2 is: 0.8-1.2 g: 1.8-2.2 g: 40-50 mL: 8-10 g: 25-35 mL;

[0017] Preferably, in the method for preparing the graphene oxide solid, the mass volume ratio of NaNO3, graphite, H2SO4, KMnO4:H2O2 is: 1 g: 2 g: 46 mL: 9 g: 30 mL.

[0018] In one embodiment, the hot stamping anti-oxidation electrochemical aluminum film further has a protective layer between the release layer and the color layer.

[0019] In one embodiment, the protective layer is made of styrene-maleic anhydride copolymer, modified PU and isocyanate;

[0020] And / or, the thickness of the protective layer is 1-3 μm;

[0021] And / or, the thickness of the substrate film layer is 10-20 μm

[0022] And / or, the material of the substrate film layer is PET;

[0023] And / or, the thickness of the release layer is 0.45±0.015 μm;

[0024] And / or, the release layer is made of silicone resin methyl branched silicone oil;

[0025] And / or, the thickness of the color layer is 1-3 μm;

[0026] And / or, the material of the color layer is melamine-formaldehyde resin or silicone resin;

[0027] And / or, the thickness of the aluminum plating layer is 1-5 μm;

[0028] And / or, the material of the aluminum-plated layer is 99.9% aluminum wire;

[0029] And / or, the thickness of the adhesive layer is 0.8-1.5 μm;

[0030] And / or, the material of the adhesive layer is methacrylate, nitrocellulose, or polyacrylate.

[0031] In a second aspect, the present application provides a hot stamping printed product, comprising a substrate and a hot stamping layer located on the surface thereof, wherein the hot stamping layer is made by hot stamping transfer of the hot stamping anti-oxidation electrochemical aluminum film as described in any of the above embodiments.

[0032] The above-mentioned hot stamping anti-oxidation electroplated aluminum film is achieved by setting an anti-oxidation graphene film layer between the aluminum plating layer and the adhesive layer. The main component of the anti-oxidation graphene film layer is graphene. Graphene does not react with acids or alkalis and has excellent chemical inertness and chemical stability. At the same time, graphene also has in-plane impermeability, which makes it impossible for substances in the solution to penetrate, so it can play an excellent physical isolation and anti-oxidation role. The high thermal conductivity of graphene can also avoid the problem of poor heat dissipation of the substrate caused by the addition of the coating. By having a protective layer between the release layer and the color layer, a thin film is formed on the surface of the color layer, so that the electroplated aluminum will not fly gold and powder after transfer, protect the color layer, improve the flexibility of the electroplated aluminum, and increase the wear resistance of the surface. The present application can solve the problem of excessive melting of silicone resin peeling layer and adhesive due to the hot stamping temperature in hot stamping production by respectively setting a protective layer and an anti-oxidation graphene film layer in the hot stamping anti-oxidation electrochemical aluminum film, better protect the aluminum-plated layer, solve the problem of oxidation corrosion of the aluminum layer, and avoid plate sticking. At the same time, through the protection of the protective layer, the problem of degradation of the quality of the hot stamping product due to oxidation polymerization of synthetic resin and dye in the color layer can be avoided, and the problem of blistering or fogging of the imprint can be solved, thereby improving the quality of hot stamping. Compared with the prior art, the present invention has the following characteristics: exquisite hot stamping graphics and texts, anti-oxidation and corrosion resistance of hot stamping graphics and texts; reasonable structural design, simple structure, and convenient drag operation; the high thermal conductivity of graphene can solve the problem of poor heat dissipation of the substrate caused by the addition of the coating; the film preparation method is green and environmentally friendly; the graphene film preparation makes it have similar performance while reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic structural diagram of a hot stamping anti-oxidation electrochemical aluminum film according to an embodiment;

[0034] Figure 2 A schematic diagram of a process for preparing an anti-oxidation graphene film layer of a hot stamping anti-oxidation electrochemical aluminum film according to an embodiment;

[0035] Figure 3 This is a finished product picture of the anti-oxidation graphene film layer of the hot stamping anti-oxidation electrochemical aluminum film according to one embodiment. DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the present application, in order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application, and the preferred implementation methods of the present application are given in the accompanying drawings. However, the present application can be implemented in many different forms and is not limited to the implementation methods described herein. On the contrary, the purpose of providing these implementation methods is to make the disclosure of the present application more thoroughly and comprehensively understood. The present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited to the specific embodiments disclosed below. It should be noted that when an element is referred to as "fixed to" another element, it can be directly on another element or there can also be a centered element. When an element is considered to be "connected" to another element, it can be directly connected to another element or there may be a centered element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are only for illustrative purposes and do not represent the only implementation method. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present application. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0037] In the first aspect, the present application provides a hot stamping anti-oxidation electrochemical aluminum film, see Figure 1 The hot stamping anti-oxidation electrolytic aluminum film includes a substrate film layer 1, a release layer 2, a protective layer 3, a color layer 4, an aluminum plating layer 5, an anti-oxidation graphene film layer 6 and an adhesive layer 7 which are connected in sequence.

[0038] In the present application, the hot stamping anti-oxidation electroplated aluminum film is provided with an anti-oxidation graphene film layer between the aluminum plating layer and the adhesive layer. The main component of the anti-oxidation graphene film layer is graphene. Graphene does not react with acids or alkalis, and has excellent chemical inertness and chemical stability. At the same time, graphene also has in-plane impermeability, so that substances in the solution cannot penetrate, so it can play an excellent physical isolation and anti-oxidation role. The high thermal conductivity of graphene can also avoid the problem of poor heat dissipation of the substrate caused by the addition of the coating. By having a protective layer between the release layer and the color layer, a thin film is formed on the surface of the color layer, so that the electroplated aluminum does not fly gold and powder after transfer, protects the color layer, improves the flexibility of the electroplated aluminum, and increases the wear resistance of the surface. The present application can solve the problem of excessive melting of silicone resin peeling layer and adhesive due to the hot stamping temperature in hot stamping production by respectively setting a protective layer and an anti-oxidation graphene film layer in the hot stamping anti-oxidation electrochemical aluminum film, better protect the aluminum-plated layer, solve the problem of oxidation corrosion of the aluminum layer, and avoid plate sticking. At the same time, through the protection of the protective layer, the problem of degradation of the quality of the hot stamping product due to oxidation polymerization of synthetic resin and dye in the color layer can be avoided, and the problem of blistering or fogging of the imprint can be solved, thereby improving the quality of hot stamping. Compared with the prior art, the present invention has the following characteristics: exquisite hot stamping graphics and texts, anti-oxidation and corrosion resistance of hot stamping graphics and texts; reasonable structural design, simple structure, and convenient drag operation; the high thermal conductivity of graphene can solve the problem of poor heat dissipation of the substrate caused by the addition of the coating; the film preparation method is green and environmentally friendly; the graphene film preparation makes it have similar performance while reducing production costs.

[0039] In one embodiment, the thickness of the anti-oxidation graphene film layer is 5-15 microns, and preferably, the thickness of the anti-oxidation graphene film layer is 12 microns. For example, the material of the protective layer is styrene-maleic anhydride copolymer, modified PU and isocyanate. For example, the thickness of the protective layer is 1-3 μm; in this way, the use of the above anti-oxidation graphene film layer and protective layer can further improve the quality of hot stamping. For example, the protective layer adopts a coating production process to form a thin film on the surface of the color layer, so that the electrochemical aluminum does not fly gold and powder after transfer, and protects the color layer. Improve the flexibility of electrochemical aluminum and increase the wear resistance of the surface; for example, the anti-oxidation graphene film layer uses a new coating technology, and graphene does not react with acid and alkali, and has excellent chemical inertness and chemical stability. At the same time, graphene also has in-plane impermeability, so that the substances in the solution cannot penetrate, so it can play an excellent physical isolation and anti-oxidation role. The high thermal conductivity of graphene can also avoid the problem of poor heat dissipation of the substrate caused by the addition of coating.

[0040] In one embodiment, the thickness of the substrate film layer is 10-20 μm. For example, the material of the substrate film layer is PET (Polyethylene terephthalate). In this way, the substrate film plays a role in supporting each coating layer, and has a smooth, bright and transparent surface, is resistant to high temperatures, has high tensile strength, and is resistant to organic solvents.

[0041] In one embodiment, the thickness of the release layer is 0.45±0.015 μm; for example, the material of the release layer is silicone methyl branched silicone oil; in this way, the release layer can enable the electrochemical aluminum coating to be well peeled off from the base film and transferred to the object to be hot-stamped. The coating amount of the release layer determines the tightness during peeling and determines the effect of hot-stamping.

[0042] In one embodiment, the thickness of the color layer is 1-3 μm; for example, the material of the color layer is melamine resin or silicone resin; for example, the color layer adopts a coating production process to form a resin film on the aluminum plating layer to determine the color of the electroplated aluminum. The coating of the color layer determines the surface effect of the electroplated aluminum. The resin of the coating determines the brightness, surface hardness, toughness, cutting performance, high temperature resistance, etc. after transfer.

[0043] In one embodiment, the thickness of the aluminum-plated layer is 1-5 μm; for example, the material of the aluminum-plated layer is 99.9% aluminum wire; in the present application, the aluminum-plated layer adopts a vacuum aluminum-plating production process to make the electrochemical aluminum emit a shiny metallic luster, making the color of the color layer more brilliant.

[0044] In one embodiment, the thickness of the adhesive layer is 0.8-1.5 μm; for example, the material of the adhesive layer is methacrylate, nitrocellulose, or polyacrylate. The adhesive layer is produced by a coating process to bond the electroplated aluminum and the object to be scalded.

[0045] In order to further ensure the quality of the graphene oxide film layer and simplify the preparation process of the graphene film layer, in one embodiment, the preparation method of the graphene oxide film layer is as follows: disperse the graphene oxide solid with ultrapure water, drip it on the PTFE film, dry it at high temperature and separate it from the PTFE film to obtain the graphene oxide film layer. For example, in one embodiment, the mass volume ratio of the graphene oxide solid to the ultrapure water is: 0.1-0.2g: 100ml; preferably, the mass volume ratio of the graphene oxide solid to the ultrapure water is: 0.15g: 100ml. In a specific embodiment, 0.15g of graphene oxide solid (graphene oxide, GO) is weighed and put into a beaker, 100mL of ultrapure water is measured and added to the beaker, and after ultrasonic dispersion for 2 hours, 5mL is dripped onto a polytetrafluoroethylene (PTFE) sheet with a 5×5cm rectangular frame (frame thickness of 1mm) surrounded by transparent tape, as shown in step 2 (a). Before drop coating, sand the PTFE with sandpaper to 5000# sandpaper, and polish it with diamond polishing paste with a particle size of 0.5 μm. After using a glass rod to evenly spread the added liquid, put the PTFE sheet into a blast drying oven, as shown in Figure 2 (b), and dry it at 60°C for 2 hours. After drying (2 (c)), use a utility knife to cut the film and the frame to remove the GO film (2 (d)). The final GO film is brown-yellow, has a certain degree of light transmittance, and is 12 μm thick. Please refer to Figure 3 , which is the finished graphene oxide film layer prepared in this application, and then the above-mentioned graphene oxide film layer can be directly used in the hot stamping anti-oxidation electrochemical aluminum film.

[0046] In order to further ensure the quality of the graphene oxide solid and simplify the production process, in one embodiment, the preparation method of the graphene oxide solid is as follows:

[0047] NaNO3, graphite, and H2SO4 are mixed, KMnO4 is added, ultrapure water is added dropwise after the reaction, and the mixture is heated for reaction, and H2O2 is added after cooling to room temperature; after standing, the mixture is centrifuged to remove the liquid to obtain a precipitate, the precipitate is mixed with hydrochloric acid and centrifuged again, the precipitate is aqueous to a neutral pH, and then freeze-dried to prepare the graphene oxide solid. In this way, the graphene oxide solid can be prepared well, the production process is green and environmentally friendly, and the production cost is reduced while ensuring similar performance.

[0048] In one embodiment, the preparation method of the graphene oxide solid is as follows: NaNO3, graphite, and H2SO4 are mixed in an ice bath, KMnO4 is added to react in an ice bath for 5-6 hours, the temperature is raised to 35±3°C for reaction for 45 minutes, ultrapure water is added dropwise after the reaction, and the reaction is heated to 100°C for 30 minutes, ultrapure water is added dropwise to the reaction liquid, and H2O2 is added slowly and uniformly after cooling to room temperature; after standing, the mixed solution is centrifuged to remove the liquid to obtain a precipitate, the precipitate is added with 4 vol% hydrochloric acid and mixed, and centrifuged again, the precipitate is aqueous to pH neutral, and then freeze-dried to prepare the graphene oxide solid. In this way, the graphene oxide solid can be better prepared, the production process is green and environmentally friendly, and the production cost is reduced while ensuring similar performance.

[0049] In one embodiment, in the preparation method of the graphene oxide solid, the mass volume ratio of NaNO3, graphite, H2SO4, KMnO4: H2O2 is: 0.8-1.2 g: 1.8-2.2 g: 40-50 mL: 8-10 g: 25-35 mL; preferably, in the preparation method of the graphene oxide solid, the mass volume ratio of NaNO3, graphite, H2SO4, KMnO4: H2O2 is: 1 g: 2g: 46 mL: 9 g: 30 mL. In this way, the graphene oxide solid can be well prepared, the production process is green and environmentally friendly, and the production cost is reduced while ensuring similar performance. Moreover, when the prepared graphene oxide solid is subsequently used in the graphene oxide film layer, graphene does not react with acid or alkali, and has excellent chemical inertness and chemical stability. At the same time, graphene also has in-plane impermeability, which makes the substances in the solution unable to penetrate, so it can play an excellent physical isolation and anti-oxidation role. The high thermal conductivity of graphene can also avoid the problem of poor heat dissipation of the substrate caused by the addition of coating.

[0050] In a specific embodiment, the process of making the graphene oxide film layer includes the following steps: Figure 2 For the steps shown, see Figure 2 , GO film preparation flow chart: (a) preparing polytetrafluoroethylene plate; (b) coating with GO solution; (c) drying; (d) peeling off the film.

[0051] This application adopts Hummer's method to prepare GO: 1 g NaNO3 and 2 g graphite are accurately weighed and added to a three-necked flask; the flask is placed in an ice water bath, 46 mL H2SO4 (98 wt%) is measured and added to the flask and a magnet is placed, the magnetic stirring speed is set to 250 rpm, and the reaction time is 45 minutes (pre-oxidation stage); 9 g KMnO4 is accurately weighed and slowly and uniformly added to the flask, and the ice water bath is continued, the magnetic stirring speed remains unchanged, and the reaction is carried out for 5.5 hours (low-temperature oxidation stage); the temperature is raised to 35±3°C, the magnetic stirring speed remains unchanged, and the reaction is carried out for 45 minutes; 92 mL ultrapure water is added dropwise and uniformly to the flask, smoke is generated in the flask during the addition, and the color of the liquid first changes from black to purple-red, and then to yellow-brown, the temperature is raised to 100°C, the magnetic stirring is continued, and the reaction is carried out for 30 minutes (high-temperature oxidation stage); heating is stopped, and 280 mL of H2SO4 is added dropwise and uniformly to the flask. Ultrapure water, magnetic stirring speed increased to 450 rpm; after cooling to room temperature, 30 mL H2O2 was slowly and uniformly added to the flask in order to dissolve the residual reducing agent in the liquid after reaction. After standing for 30 minutes, the liquid turned bright yellow; the liquid was put into a centrifuge tube, centrifuged at 4000 rpm for 5 minutes, and the liquid was removed; 4 vol% dilute hydrochloric acid was added to the centrifuge tube, shaken and centrifuged at 4000 rpm for 5 minutes, and the liquid was removed; ultrapure water was added to the centrifuge tube, shaken and centrifuged, the liquid was removed, and the washing was repeated 5 times until the liquid pH = 7. The first two centrifugation speeds and times were both 4000 rpm for 5 minutes, the third was 7000 rpm for 5 minutes, the fifth and sixth centrifugation speeds were both 12000 rpm, the fifth centrifugation time was 10 minutes, and the sixth was 20 minutes; the final product was vacuum freeze-dried for 96 hours to obtain GO solid.

[0052] Weigh 0.15 g of GO into a beaker, measure 100 mL of ultrapure water and add it to the beaker. After ultrasonic dispersion for 2 hours, add 5 mL to a polytetrafluoroethylene (PTFE) sheet with a 5×5 cm rectangular frame (frame thickness of 1 mm) surrounded by transparent tape, as shown in step 2 (a). Before drop coating, use sandpaper to grind the PTFE to 5000# sandpaper and polish it with diamond polishing paste with a particle size of 0.5 μm. Use a glass rod to evenly spread the added liquid, then place the PTFE sheet in a forced air drying oven, as shown in step 2 (b), and dry it at 60°C for 2 hours. After drying (step 2 (c) in Figure 2), use a utility knife to cut the film and the frame to remove the GO film (step 2 (d) in Figure 2). The final GO film is brown-yellow, has a certain degree of transmittance, and is 12 μm thick. Please refer to Figure 3, which is a finished photo of the graphene oxide film layer prepared in this application.

[0053] A specific embodiment of a hot stamping anti-oxidation electrochemical aluminum film is provided below.

[0054] Example 1

[0055] A hot stamping anti-oxidation electrolytic aluminum film comprises a substrate film, a release layer, a protective layer, a color layer, an aluminum plating layer, an anti-oxidation graphene film layer, and an adhesive layer.

[0056] The thickness of the substrate film layer is (10-20μm); the material is PET;

[0057] The thickness of the release layer is (0.45 μm); silicone resin methyl branched silicone oil;

[0058] The thickness of the protective layer is (2 μm); styrene-maleic anhydride copolymer, modified PU, isocyanate;

[0059] The thickness of the color layer is (2μm); the material is melamine-formaldehyde resin and silicone resin;

[0060] The thickness of the aluminum coating is (2μm); the material is 99.9% aluminum wire.

[0061] The thickness of the anti-oxidation graphene film layer is (12 μm); the material is: graphene;

[0062] The thickness of the adhesive layer is (1.0μm); the material is methacrylate, nitrocellulose, and polyacrylate.

[0063] In Example 1, the substrate film plays a role in supporting each coating, and the surface is smooth, bright and transparent, high temperature resistant, with high tensile strength and resistance to organic solvents; the release layer can make the electroplated aluminum coating be well peeled off from the base film and transferred to the hot stamped object. The coating amount of the release layer determines the tightness during peeling and the effect of hot stamping; the protective layer adopts a coating production process to form a thin film on the surface of the color layer, so that the electroplated aluminum will not fly gold and powder after transfer, and protect the color layer. Improve the flexibility of the electroplated aluminum and increase the wear resistance of the surface; the color layer adopts a coating production process to form a layer of resin film on the aluminum-plated layer to determine the color of the electroplated aluminum. The coating of the color layer determines the surface effect of the electroplated aluminum. The resin of the coating determines the brightness, surface hardness, toughness, cutting performance, high temperature resistance, etc. after transfer; the aluminum-plated layer adopts a vacuum aluminum-plating production process to make the electroplated aluminum emit a shiny metallic luster, which makes the color of the color layer more brilliant. The anti-oxidation graphene film layer uses a new coating technology, and graphene does not react with acids and alkalis, and has excellent chemical inertness and chemical stability. At the same time, graphene also has in-plane impermeability, which makes the substances in the solution unable to penetrate, so it can play an excellent physical isolation and anti-oxidation role. The high thermal conductivity of graphene can also avoid the problem of poor heat dissipation of the substrate caused by the addition of coating. The adhesive layer adopts the coating production process to bond the electroplated aluminum and the object to be scalded.

[0064] The preparation process of the anti-oxidation graphene film layer of Example 1 is as follows: This application adopts Hummer's method to prepare GO: 1 g NaNO3 and 2 g graphite are accurately weighed and added to a three-necked flask; the flask is placed in an ice water bath, 46 mL H2SO4 (98 wt%) is measured and added to the flask and a magnet is placed, the magnetic stirring speed is set to 250 rpm, and the reaction time is 45 minutes (pre-oxidation stage); 9 g KMnO4 is accurately weighed and slowly added to the flask at a uniform speed, and the ice water bath is continued, the magnetic stirring speed remains unchanged, and the reaction is carried out for 5.5 hours (low-temperature oxidation stage); the temperature is raised to 35±3°C, the magnetic stirring speed remains unchanged, and the reaction is carried out for 45 minutes; 92 mL ultrapure water is added dropwise to the flask at a uniform speed, smoke is generated in the flask during the addition, and the color of the liquid first changes from black to purple-red, and then to yellow-brown, the temperature is raised to 100°C, the magnetic stirring is continued, and the reaction is carried out for 30 minutes (high temperature oxidation stage); stop heating, add 280mL ultrapure water dropwise to the flask at a uniform speed, and increase the magnetic stirring speed to 450 rpm; after cooling to room temperature, slowly and uniformly add 30 mL H2O2 to the flask in order to dissolve the residual reducing agent in the liquid after reaction. After standing for 30 minutes, the liquid turns bright yellow; put the liquid into a centrifuge tube, centrifuge at 4000 rpm for 5 minutes, and remove the liquid; add 4 vol% dilute hydrochloric acid to the centrifuge tube, shake well and centrifuge at 4000 rpm for 5 minutes, and remove the liquid; add ultrapure water to the centrifuge tube, shake well and centrifuge, remove the liquid, and repeat the washing 5 times until the liquid pH = 7. The first two centrifugation speeds and times are both 4000 rpm for 5 minutes, the third is 7000 rpm for 5 minutes, the fifth and sixth centrifugation speeds are both 12000 rpm, the fifth centrifugation time is 10 minutes, and the sixth is 20 minutes; the final product is vacuum freeze-dried for 96 hours to obtain GO solid. Weigh 0.15 g of GO into a beaker, measure 100 mL of ultrapure water and add it to the beaker. After ultrasonic dispersion for 2 hours, add 5 mL to a polytetrafluoroethylene (PTFE) sheet with a 5×5 cm rectangular frame (frame thickness of 1 mm) surrounded by transparent tape, as shown in step 2 (a). Before drop coating, use sandpaper to grind the PTFE to 5000# sandpaper and polish it with diamond polishing paste with a particle size of 0.5 μm. Use a glass rod to evenly spread the added liquid, then place the PTFE sheet in a forced air drying oven, as shown in step 2 (b), and dry it at 60°C for 2 hours. After drying (step 2 (c) in Figure 2), use a utility knife to cut the film and the frame to remove the GO film (step 2 (d) in Figure 2). The final GO film is brown-yellow, has a certain degree of transmittance, and is 12 μm thick. Please refer to Figure 3, which is a finished photo of the graphene oxide film layer prepared in this application.

[0065] The hot stamping anti-oxidation electrochemical aluminum film of Example 1 was subjected to various performance tests, and the test results are shown in the following table:

[0066] Table 2 Test results of various properties of the hot stamping anti-oxidation electrochemical aluminum film of Example 1

[0067] As can be seen from the above, the hot stamping anti-oxidation electrochemical aluminum film provided by the present application has undergone an anti-oxidation test, and is free of oxidation, stains, and blackening, which effectively improves the anti-oxidation quality. It has undergone abrasion resistance tests and adhesion tests, and has also undergone alkali resistance tests, acid resistance tests, and water resistance tests, which better ensures the quality of hot stamping transfer printing. Moreover, the hot stamping transfer of the present application has a high yield rate and a low defect rate, which better ensures the product quality.

[0068] The above-mentioned hot stamping anti-oxidation electroplated aluminum film is achieved by setting an anti-oxidation graphene film layer between the aluminum plating layer and the adhesive layer. The main component of the anti-oxidation graphene film layer is graphene. Graphene does not react with acids or alkalis and has excellent chemical inertness and chemical stability. At the same time, graphene also has in-plane impermeability, which makes it impossible for substances in the solution to penetrate, so it can play an excellent physical isolation and anti-oxidation role. The high thermal conductivity of graphene can also avoid the problem of poor heat dissipation of the substrate caused by the addition of the coating. By having a protective layer between the release layer and the color layer, a thin film is formed on the surface of the color layer, so that the electroplated aluminum will not fly gold and powder after transfer, protect the color layer, improve the flexibility of the electroplated aluminum, and increase the wear resistance of the surface. The present application can solve the problem of excessive melting of silicone resin peeling layer and adhesive due to the hot stamping temperature in hot stamping production by respectively setting a protective layer and an anti-oxidation graphene film layer in the hot stamping anti-oxidation electrochemical aluminum film, better protect the aluminum-plated layer, solve the problem of oxidation corrosion of the aluminum layer, and avoid plate sticking. At the same time, through the protection of the protective layer, the problem of degradation of the quality of the hot stamping product due to oxidation polymerization of synthetic resin and dye in the color layer can be avoided, and the problem of blistering or fogging of the imprint can be solved, thereby improving the quality of hot stamping. Compared with the prior art, the present invention has the following characteristics: exquisite hot stamping graphics and texts, anti-oxidation and corrosion resistance of hot stamping graphics and texts; reasonable structural design, simple structure, and convenient drag operation; the high thermal conductivity of graphene can solve the problem of poor heat dissipation of the substrate caused by the addition of the coating; the film preparation method is green and environmentally friendly; the graphene film preparation makes it have similar performance while reducing production costs.

[0069] In a second aspect, the present application provides a hot stamping printed product, comprising a substrate and a hot stamping layer on the surface thereof, wherein the hot stamping layer is made by hot stamping transfer of the hot stamping anti-oxidation electrochemical aluminum film as described in any of the above embodiments. In other words, the hot stamping anti-oxidation electrochemical aluminum film of the present application is used in hot stamping printed products.

[0070] 1. Compared with the prior art, the present invention has the characteristics of exquisite hot stamping images and texts, and anti-oxidation and corrosion resistance;

[0071] 2. Reasonable structural design, simple structure, easy to operate;

[0072] 3. The high thermal conductivity of graphene can solve the problem of poor heat dissipation of the substrate caused by the addition of coating;

[0073] 4. The film preparation method is green and environmentally friendly;

[0074] Preparation of graphene films to make them similar in performance while reducing production costs;

[0075] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. It should be noted that "in one embodiment", "for example", "for example", etc. in this application are intended to illustrate the present application, rather than to limit the present application. The above-described embodiments only express several implementation methods of the present application, and the description is relatively specific and detailed, but it cannot be understood as a limitation on the scope of the patent application. It should be pointed out that for a person of ordinary skill in the art, without departing from the concept of the present application, several variations and improvements can also be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be subject to the attached claims.

Claims

1. A hot stamping anti-oxidation electrochemical aluminum film, comprising a substrate film layer, a release layer, a color layer, an aluminum plating layer and an adhesive layer connected in sequence, characterized in that: An anti-oxidation graphene film layer is provided between the aluminum plating layer and the adhesive layer.

2. The hot stamping anti-oxidation electrochemical aluminum film according to claim 1, characterized in that: The thickness of the anti-oxidation graphene film layer is 5-15 microns. And / or, a protective layer is provided between the release layer and the color layer.

3. The hot stamping anti-oxidation electrochemical aluminum film according to claim 1, characterized in that: The thickness of the protective layer is 1-3 μm; And / or, the thickness of the anti-oxidation graphene film layer is 12 microns; And / or, the material of the protective layer is styrene-maleic anhydride copolymer, modified PU and isocyanate.

4. The hot stamping anti-oxidation electrochemical aluminum film according to claim 1, characterized in that: The preparation method of the graphene oxide film layer is as follows: The graphene oxide solid is dispersed in ultrapure water, and then drop-coated on a PTFE film, dried at high temperature, and separated from the PTFE film to obtain the graphene oxide film layer.

5. The hot stamping anti-oxidation electrochemical aluminum film according to claim 4, characterized in that: The mass volume ratio of the graphene oxide solid to the ultrapure water is: 0.1-0.2 g: 100 ml; Preferably, the mass volume ratio of the graphene oxide solid to the ultrapure water is: 0.15g:100ml.

6. The hot stamping anti-oxidation electrochemical aluminum film according to claim 4, characterized in that: The preparation method of the graphene oxide solid is as follows: NaNO3, graphite and H2SO4 are mixed, KMnO4 is added, ultrapure water is added dropwise after the reaction, and the mixture is heated for reaction. After cooling to room temperature, H2O2 is added; after standing, the mixture is centrifuged to remove the liquid to obtain a precipitate, hydrochloric acid is added to the precipitate, the mixture is mixed and centrifuged again, the precipitate is diluted to a neutral pH, and then freeze-dried to prepare the graphene oxide solid.

7. The hot stamping anti-oxidation electrochemical aluminum film according to claim 6, characterized in that: The preparation method of the graphene oxide solid is as follows: NaNO3, graphite, and H2SO4 are mixed in an ice bath, KMnO4 is added and reacted in an ice bath for 5-6 hours, the temperature is raised to 35±3°C and reacted for 45 minutes, ultrapure water is added dropwise after the reaction, and the mixture is heated to 100°C and reacted for 30 minutes, ultrapure water is added dropwise to the reaction solution, H2O2 is added slowly and uniformly after cooling to room temperature; after standing, the mixed solution is centrifuged to remove the liquid to obtain a precipitate, 4 vol% hydrochloric acid is added to the precipitate, the mixture is mixed and centrifuged again, the precipitate is aqueous to a neutral pH, and then freeze-dried to obtain the graphene oxide solid.

8. The hot stamping anti-oxidation electrochemical aluminum film according to claim 7, characterized in that: In the preparation method of the graphene oxide solid, the mass volume ratio of NaNO3, graphite, H2SO4, KMnO4: H2O2 is: 0.8-1.2 g: 1.8-2.2 g: 40-50 mL: 8-10 g: 25-35 mL; Preferably, in the method for preparing the graphene oxide solid, the mass volume ratio of NaNO3, graphite, H2SO4, KMnO4:H2O2 is: 1 g: 2 g: 46 mL: 9 g: 30 mL.

9. The hot stamping anti-oxidation electrochemical aluminum film according to any one of claims 1 to 8, characterized in that: The thickness of the substrate film layer is 10-20 μm And / or, the material of the substrate film layer is PET; And / or, the thickness of the release layer is 0.45±0.015 μm; And / or, the release layer is made of silicone resin methyl branched silicone oil; And / or, the thickness of the color layer is 1-3 μm; And / or, the material of the color layer is melamine-formaldehyde resin or silicone resin; And / or, the thickness of the aluminum plating layer is 1-5 μm; And / or, the material of the aluminum-plated layer is 99.9% aluminum wire; And / or, the thickness of the adhesive layer is 0.8-1.5 μm; And / or, the material of the adhesive layer is methacrylate, nitrocellulose, or polyacrylate.

10. A hot stamping printed product, characterized in that: The invention comprises a substrate and a hot stamping layer on the surface of the substrate, wherein the hot stamping layer is made by hot stamping transfer printing of the hot stamping anti-oxidation electrochemical aluminum film as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Aluminizer film for gold stamping

    CN106113961A

Cited By

  • Corrosion-resistant two-component adhesive as well as preparation method and application thereof

    CN122686275A

  • A gilding film adhesive, its preparation method and application

    CN122854971A